Determination of Air Stability Parameter Threshold Value for Cumulonimbus and Thunderstorm Cloud Events at Kualanamu Meteorological Station - Prima, Rajab; Arifianto, Fendy; Donni H, Yosafat; Avrionesti, Avrionesti (Journal of Technomaterial Physics, 2023)
Many studies have carried out calculations related to atmospheric lability as a reference in weather forecasts, especially cumulonimbus clouds, and thunderstorms. However, many air lability index values are found to be inappropriate in each region because conditions in each region are different from each other in the region. So it is necessary to use precise index thresholds to determine weather conditions. In the study, observational data and data from Showalter Index (SI), Lifted Index (LI), K Index (KI), Severe Weather Threat Index (SWEAT), and Convective data were used. Available Potential Energy (CAPE) for ten years (2013-2022), then statistical calculations and verification for one year (2022) are carried out. The results obtained are the atmospheric stability index with the best accuracy in predicting the presence of cumulonimbus clouds and thunderstorms at the Kualanamu Meteorological Station, Deli Serdang is the best LI index to predict TS 00 and TS 12, and the best KI index to predict CB 00 and CB 12.